Implementation of Moral Education Values Through Amaliyah An Nahdliyah in Islamic Boarding Schools - Ilmia, Siti Lailatul; Mustajab, Mustajab; Subakri, Subakri (EDUTEC : Journal of Education And Technology, 2025)
The advancement of time, globalization, and digitalization present challenges for educational institutions, including Islamic boarding schools (Pesantren), in preserving the values of moral education. This study aims to explain the integration of moral education values through Amaliyah An Nahdliyah at Lathiful Amien Islamic Boarding School, Lumajang. The research focuses on: 1) activities related to moral education values through Amaliyah An Nahdliyah, 2) its relevance, and 3) the outcomes of its implementation. A descriptive qualitative method was employed, with data collection techniques including observation, interviews, and documentation. Data analysis utilized the Miles-Huberman and Saldana interactive model, encompassing data collection, condensation, presentation, and conclusion drawing. The data condensation process involved selecting, simplifying, and transforming information. Data validity was ensured through triangulation of techniques and sources. The findings indicate that Amaliyah An Nahdliyah holds strong relevance in shaping students’ morals and has a positive impact on the implementation of Islamic education values in the digital era.